Provable secure mutual RFID authentication protocol based on QC-MDPC code - Ze-hui LI; Ya-tao YANG; Zi-chen LI (Tongxin xuebao)
The security of radio frequency identification (RFID) has become an increasingly severe issue.In order to protect the security of information interaction in wireless channel of RFID system,a mutual RFID authentication secure protocol was proposed.It was like the Niederreiter type public cryptography which based on the quasi-cyclic medium density parity check code(QC-MDPC).The security proof for this novel protocol was given by using a reduction method ，and the hardness of attacking was reduced to the decoding problem of the linear codes.Besides the performance results also exhibit that compared with other RFID authentication protocols,this protocol is more suitable for RFID system in areas of interaction,computation and storage,which owns limited resource and needs high efficiency.